PREVALENCE OF VITAMIN D AND SERUM CALCIUM, PHOSPHORUS AND ALKALINE PHOSPHATASE IN PEDIATRIC POPULATION OF KANCHEEPURAM DISTRICT, TAMILNADU. - KIRAN B,; PREMA A,; THILAGAVATHI R,; JAMUNA RANI R, (International Journal of Pharma and Bio Sciences, 2015)
Vitamin D deficiency has become the emerging threat to modern medicine. Globally, around 29-100% of children and adolescents have Vitamin D deficiency.The objective of current study is to find out the prevalence of Vitamin D deficiency and calcium, phosphorus and alkaline phosphatase in pediatric population of Kancheepuram District, Tamilnadu. Healthy children of both sexes between the age of 1-17 living in and around Potheri village was included. Total of 100 subjects, out of which 50 males and 50females were recruited. 2 ml of the blood was drawn and serum levels of Vitamin D, calcium, phosphorus and alkaline phosphatase were estimated. Prevalence of Vitamin D deficiency in healthy children was 59%, insufficiency and normal levels were 36% and 5% respectively. Prevalence of Vitamin D deficiency is alarming in the Kancheepuram district and government should intervene and create awareness to address this public health problem on a priority basis.